Buyer-supplier collaboration: A macro, micro, and congruence perspective. Issue 1 (January 2022) - Li, Mei; Falcone, Ellie; Sanders, Nada; Choi, Thomas Y.; Chang, Xiangyu
Abstract: Buyer-supplier collaboration, an important part of operational performance, is predicated on the assumption that a firm's stated strategy on inter-firm collaboration is implemented in practice. We argue that a strategy is only as good as its execution and that micro-level factors—the employees' collaborative propensity and their internal collaborative behaviors—also play an essential role in the successful implementation of buyer-supplier collaboration. We test competing models based on secondary data collected from 330 manufacturing firms in 16 countries/regions. Our results show that both the macro-level firm strategy and micro-level employee factors exert substantial influence over buyer-supplier collaboration. In addition, when inter-firm collaborative strategy and micro-level factors are congruent, there is an enhancement effect. Our research explores the critical role of supply managers and surrounding employees in shaping buyer-supplier collaboration and actualizing operational strategies. Highlights: Building a collaborative relationship with suppliers requires more than setting up a collaborative policy. Supply manager's collaborative propensity matters. Surrounding employees' collaborative behaviors matters. Buyer-supplier collaboration is best realized when there is a congruence of these factors.